2022
DOI: 10.1002/ange.202205301
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Metal Complexes for Electrocatalytic Carbon Dioxide Reduction: From Adjustment of Intrinsic Activity to Molecular Immobilization

Abstract: The electrocatalytic CO 2 reduction reaction (ECO 2 RR) is one promising method for storing intermittent clean energy in chemical bonds and producing fuels. Among various kinds of catalysts for ECO 2 RR, molecular metal complexes with well-defined structures are convenient for studies of their rational design, structure-reactivity relationships, and mechanisms. In this Review, we summarize the molecular engineering of several N-based metal complexes including Re/Mn bipyridine compounds and metal macrocycles, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 185 publications
0
2
0
Order By: Relevance
“…21 Such behavior facilitates the homogeneous molecular catalysts to effectively cover the gas−liquid interface, aiding in the efficient storage and transfer of electrons for electrochemical reactions. 36 The structure and derivatives of this molecular catalyst have been extensively studied, 37−40 enabling us to trace and identify its evolution in microdroplets. Gas mass flow controllers are employed to accurately control the gas flow rate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Such behavior facilitates the homogeneous molecular catalysts to effectively cover the gas−liquid interface, aiding in the efficient storage and transfer of electrons for electrochemical reactions. 36 The structure and derivatives of this molecular catalyst have been extensively studied, 37−40 enabling us to trace and identify its evolution in microdroplets. Gas mass flow controllers are employed to accurately control the gas flow rate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous studies have indicated that in the presence of an electric field, polar solute molecules tend to occupy the entire surface of microdroplets . Such behavior facilitates the homogeneous molecular catalysts to effectively cover the gas–liquid interface, aiding in the efficient storage and transfer of electrons for electrochemical reactions . The structure and derivatives of this molecular catalyst have been extensively studied, enabling us to trace and identify its evolution in microdroplets.…”
Section: Resultsmentioning
confidence: 99%